In Vitro Anti-Inflammatory Activity of Bajakah Tampala Root (Spatholobus littoralis Hassk.) - Maskur, Sri Karina; Tahir, Masdiana; Razak, Rais (Pharmaceutical Reports, 2025)
Bajakah tampala root (Spatholobus littoralis Hassk.) contains phenolic compounds, flavonoids, tannins, terpenoids and saponins. Flavonoid compounds have pharmacological effects, namely anti-inflammatory. The purpose of this study was to determine the anti-inflammatory activity of ethanol extract of bajakah tampala root by inhibiting protein denaturation in vitro using UV-Vis spectrophotometer and diclofenac sodium as positive control. The extract was prepared by maceration method using 96% ethanol solvent. The results showed that the ethanol extract of bajakah tampala root had a percentage of inhibition of 31.27% at the lowest concentration (10 ppm) and 43.28% at the highest concentration (50 ppm) with an IC50 value of 77.92 µg/mL and the ic50 value of diclofenac sodium is 12.26 µg/mL. The percentage of inhibition that is more than 20% is considered to have inhibitory power in the protein denaturation process. So, it can be concluded that the ethanol extract of bajakah root has potential as an anti-inflammatory.